The Enduring Indians of Kansas : A Century and a Half of Acculturation - Herring, Joseph B., 1947- (Book collections on Project MUSE., 1990)
Of the 10,000 Indians forced across the Mississippi into eastern Kansas before the middle of the 19th century, a few have managed to walk the thin line between resistance to white culture and absorption into it. Herring, an archivist with the National Archive and Records Administration, tells the story of those who are still Indians, and still in Kansas.